The wild fox of Yemen : poems - Almontaser, Threa (Minneapolis, Minnesota : Graywolf Press, 2021)
By turns aggressively reckless and fiercely protective, always guided by faith and ancestry, Threa Almontaser's incendiary debut asks how mistranslation can be a form of self-knowledge and survival. A love letter to the country and people of Yemen, a portrait of young Muslim womanhood in New York after 9/11, and an extraordinarily composed examination of what it means to carry in the body the echoes of what came before, Almontaser's polyvocal collection sneaks artifacts to and from worlds, repurposing language and adapting to the space between cultures. Half-crunk and hungry, speakers move with the force of what cannot be contained by the limits of the American imagination, and instead invest in troublemaking and trickery, navigate imperial violence across multiple accents and anthems, and apply gang signs in henna, utilizing any means necessary to form a semblance of home. In doing so,The Wild Fox of Yemen fearlessly rides the tension between carnality and tenderness in the unruly human spirit.
I. Hunting girliness -- Stained skin -- Muslim girl with white guys, ending at the edge of a ridge -- Recognized language -- Etymology of hair --Shaytan sneaks bites of my tuna sandwich -- Muslim with dog -- Dream interpretation [apricot] -- Pig flesh -- Portrait of this country -- When people are cursed -- Feast, beginning w/ a kissed blade -- II. Hunger wraps himself -- Guide to gardening your roots -- Operation restoring hope -- Yemen rising as poorest country in the world -- Coffee Arabica as a maelstrom of endless aftershocks -- The snapping turtles in Ta'iz have beards -- Dream interpretation [fox] -- At the summit, he finds a nest -- Hidden bombs in my coochie -- Home security after 9/11 -- My president asks me about redemption -- III. Heritage emissary -- I thicken the room w/ dim mirrors & an altar of aliens, waiting for a sign -- My father finds home through the birds -- Dream interpretation [sea] -- After running away from another marriage proposal -- I crack an egg -- Middle Eastern music -- Please take off your shoes before entering -- And that fast, you're thinking about their bodies --Why I am silent about the lament -- Catasterism -- When white boys ask to see my hair -- Ode to bodega cats.
Keywords: 2000-2099; Arabic poetry; New York (N.Y.) -- Poetry; New York (State) -- New York; Yemen (Republic); Poetry; Poetry